Seleksi Spermatozoa Domba Garut dengan Metode Sentrifugasi Gradien Densitas Percoll - Sujoko, Heri; Agus Setiadi, Mohamad; Boediono, Arief (Jurnal Veteriner, 2009)
Preparation of a good quality of sperm is required in order to increase the efficacy of in vitro fertilization.One method of a good sperm preparation is the use of Percoll density gradient centrifugation. This studywas aimed to determine the optimal combination of speed and time of centrifugation for the spermpreparation with the lowest mortality rate. Fresh semen collected from Garut sheep with the concentrationof 2 million cells per ml was used in this study. The experimental design used was a completely randomizedfactorial design with one control group and sixteen combination of speed and time of centrifugation. Theywere 1),(1) 200 xg for 5 min; (2) 200 xg for 10 min; (3) 200 xg for 15 min; (4) 200 xg for 20 min; (5) 300 xg for5 min; (6) 300 xg for 10 min; (7) 300 xg for 15 min; (8) 300 xg for 20 min; (9) 400 xg for 5 min; (10) 400 xg for10 min; (11) 400 xg for 15 min; (12) 400 xg for 20 min; (13) 500 xg for 5 min; (14) 500 xg for 10 min; (15) 500xg for 15 min; and (16) 500 xg for 20 min. All of control and treatments combination were replicated forthree times. Each control and combined treatment were replicated for three times. The variables observedwere the concentration of sperm, the percentage of live sperms, the percentage of progressively motilesperms and the percentage of normal sperm. The data obtained were analyzed by two way analysis ofvariance (ANOVA) and the differences between treatment groups were subjected for Duncan’s MultipleRange Test (DMRT). The best result was obtained using 400 xg for 15 minutes which showed the spermconcentration of 66.66 ± 12.22 millions per ml, the living sperms of 74.82± 1.53%, the percentage ofprogressively motile sperm of 57.56±8.42% and the percentage of normal sperm of 86±1.73%).
Keywords: selection, sperms, centrifugation, percoll